2022
DOI: 10.3390/su142315881
|View full text |Cite
|
Sign up to set email alerts
|

Plant Probiotic Endophytic Pseudomonas flavescens D5 Strain for Protection of Barley Plants from Salt Stress

Abstract: Soil salinity has become a global issue that is directly related to land degradation and results in many changes in climate, ecosystem services, and biodiversity. The present study focuses on the investigation of beneficial properties of a plant probiotic bacterial strain as an eco-friendly and sustainable approach to promote crop growth in saline soil. The endophytic halotolerant strain Pseudomonas flavescens D5 isolated from common chicory (Cichorium intybus L.) was able to grow on a medium containing 15% Na… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 54 publications
0
5
0
Order By: Relevance
“…Furthermore, Ignatova et al (2022) found that the endophytic halotolerant strain Pseudomonas flavescens D5 isolated from chicory had a complex of beneficial effects on plants under abiotic stress including IAA synthesis and enzymatic activity (amylolytic, cellulolytic, and proteolytic).…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, Ignatova et al (2022) found that the endophytic halotolerant strain Pseudomonas flavescens D5 isolated from chicory had a complex of beneficial effects on plants under abiotic stress including IAA synthesis and enzymatic activity (amylolytic, cellulolytic, and proteolytic).…”
Section: Discussionmentioning
confidence: 99%
“…The objects of the study were endophytic bacterial strains isolated from the leaves of peppermint (Méntha piperíta)-Bacillus aerophilus A2 (accession number OQ569360)-and the flowers of common chicory (Cichórium intybus)-Pseudomonas flavescens D5 (accession number OP642636) [11].…”
Section: Methodsmentioning
confidence: 99%
“…Moreover, beneficial rhizosphere microorganisms in plants can not only enhance salttolerant properties but also synergistically improve plant responses to salt stress by altering physiological growth processes, including seed germination, morphological structure, and biomass accumulation and partitioning (Pan et al, 2020). Regarding the inoculation of beneficial microbial strains to help crops tolerant salinity, studies have demonstrated that inoculation with Pseudomonas flavescens D5 strain effectively increased the biomass and antioxidant enzyme activities of barley, while reducing the adverse effects of salt stress on barley (Ignatova et al, 2022). Inoculation of candidate strains of Azotobacter has also been found to increase the potassium-sodium ratio, polyphenol and chlorophyll content, and decrease proline concentration in maize, thereby alleviating salt stress in maize by integrating multiple mechanisms (Rojas-Tapias et al, 2012).…”
Section: Direct Utilization Of Soil Microorganismsmentioning
confidence: 99%